Green Building in the Arctic Region: State-of-the-Art and Future Research Opportunities - Ravasio, Lucrezia; Sveen, Svein-Erik; Riise, Raymond (Sustainability, 2020)
The concept of Green Building refers to environmentally friendly constructions with the target of minimizing the impact on the natural environment through sustainable and efficient use of resources over their life cycle. Since modern buildings are large contributors to global energy consumption and greenhouse gas emissions, policies and international strategies intended to reduce the carbon footprint of conventional buildings are highlighting the role of this recently introduced building concept. This study provides a systematic literature review of existing research related to Green Buildings in the Arctic. Despite numerous studies and projects developed during the last decades, a study describing the current research status for this region is still missing. The review first examines the role that national and international policies developed by the arctic countries have on the development process of Green Buildings. Second, it provides an overview of the most commonly used and promoted Green Building rating systems used by the same countries in the region. The analysis highlights benefits and critical issues of Green Buildings located in the Arctic in comparison with conventional buildings, focusing on environmental, economic, and social dimensions. Finally, future research opportunities are presented and discussed.